2022
DOI: 10.3389/fphar.2022.1011115
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone attenuates experimental colitis by reducing neutrophil infiltration of colonic mucosa

Abstract: Ulcerative colitis (UC) is a chronic relapsing disease featuring aberrant accumulation of neutrophils in colonic mucosa and the luminal space. Although significant advances in UC therapy have been made with the development of novel biologics and small molecules targeting immune responses, success of most current therapies is still limited, with significant safety concerns. Thus, there is a need to develop additional safe and effective therapies for the treatment of UC. Antimalarial drugs have been safely used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Additionally, the exact source of neutrophils’ deleterious effects is unclear. Some studies report impairment of neutrophil recruitment and trafficking significantly improving the pathology of colitis ( 83 , 84 ), while others have demonstrated efficacy in degrading neutrophil extracellular traps ( 85 ). Intestinal oxidative damage is prominent in both forms of IBD ( 86 88 ), and we have previously shown that deletion of Socs3 in myeloid cells leads to elevated neutrophil activation and increased production of reactive oxygen species ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the exact source of neutrophils’ deleterious effects is unclear. Some studies report impairment of neutrophil recruitment and trafficking significantly improving the pathology of colitis ( 83 , 84 ), while others have demonstrated efficacy in degrading neutrophil extracellular traps ( 85 ). Intestinal oxidative damage is prominent in both forms of IBD ( 86 88 ), and we have previously shown that deletion of Socs3 in myeloid cells leads to elevated neutrophil activation and increased production of reactive oxygen species ( 44 ).…”
Section: Discussionmentioning
confidence: 99%